Behaviour of reinforced concrete beam with silica fume understatic load with w/c ratio of 0.3 , 0.4 , 0.5 / Abd Rahim Abdul Raffar - Abdul Raffar, Abd Rahim (Faculty of Civil Engineering, 2000)
The purpose of the study is to investigate the high strength concrete beam which compressive strength is 60 N/mm2. The reinforced concrete beam is mixed to various water-cement ratios where 15% of silica fume for adding due to cement-replacement (weight). The experiment is to study the behavior of reinforced concrete beam under static load with respect to the serviceability and ultimate limit strength. An experimental program is set-up and three beams have been tested. The load is applied in two-point load onto singly reinforced concrete beam. The deflection automatically gives the measurement of crack width, and crack length. The crack width and crack length at each step loading are observed during the process. This study needs a lot of analysis of crack and design of the reinforced concrete beams which containing silica fume and varies water cement ratios.